Asymmetric Image Encryption and Authentication Based on Equal Modulus Decomposition in the Fresnel Transform Domain - Guangyu Luan; Aichuan Li; Dongmei Zhang; Dongxin Wang (IEEE Photonics Journal, 2019)
A novel asymmetric image encryption and authentication scheme based on equal modulus decomposition (EMD) in the Fresnel transform domain is proposed. First, the Fresnel spectrum of the plaintext is sparsely sampled. Then a sparse presentation of the Fresnel spectrum is divided into two complex-valued masks with equal modulus based on EMD, both of which are necessary for decryption and authentication. The decrypted image renders little information on the original image visually. Furthermore, a nonlinear correlation is used to authenticate the decrypted image with the plaintext. In the scheme proposed here, the illuminating wavelength and the diffraction distance strengthen the security of the proposed scheme significantly, and the two complex-valued masks are both essential for decryption and authentication. The percentage of extracted pixels does not have to be determined deliberately. The feasibility and validity of the scheme have been proved by numerical simulations.